A Convective Study on Heat Transfer Enhancement from Vertical Plate - Palande, D.D.; Mahalle, A.M. (Journal of Engineering and Technology (JET), 2013)
Vertical plates are the useful geometry in many applications Many authors have investigated the natural convection heat transfer from wide vertical flat plate over the past so many years. Among the geometrical variations, rectangular plates are the most commonly encountered fin geometry because of their simple construction, cheap cost and effective cooling capability. In this paper, the experimental investigation of enhancing heat transfer from vertical rectangular and V fins under natural convection condition is performed. It was investigated that partition plates of different shapes attached on vertically heated plate would create suitable fluid motion and in turn they promote the heat transfer rate. The prime objectives of this paper is to measure heat transfer coefficient of vertical fins and V-fins under natural convection. For the same height of the partition plate, V-plates have higher average heat transfer coefficient Ha than vertical partition plate.